Experimental investigation on dynamic performance of air-source heat pump water heater using R134a. (2016) - Wang, Zhihua; Wang, Fenghao; Wu, Xiaozhou; Tian, Chun
This paper describes the experiment carried out to analyse the effects of improper refrigerant charge and incorrect thermal expansion valve (TXV) opening on the ASHPWH using R134a. The performance of the system were measured in combinations of four refrigerant charges of 70%, 85%, 100% and 115% of the optimal value and three TXV opening of 30%, 45% and 60% of full opening at ambient temperature of 20°C D/15°C W (dry-bulb temperature/wet-bulb temperature). The results showed that the maximum coefficient of performances (COPs) were nearly 33%, 31.9% and 4.4% higher than that of 70%, 85% and 115% of the optimal refrigerant charge at 60% TXV opening, respectively. And it was found that the increase in TXV opening can enhance the COP when water temperature exceeded 30°C. Besides, an exergy analysis was conducted to evaluate the thermodynamic performance of the system and components in this study.